Sistem Deteksi Warna pada Quadcopter Ar.Drone Menggunakan Metode Color Filtering Hue Saturation and Value (HSV) - Ayang Setiyo Putri; Gembong Edhi Setyawan; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Currently quadcopter is widely used as one of the objects of research method using image processing. With the applied image processing on quadcopter then quadcopter will have plenty of ability to perform the mission, such as tracking, landing, or detect certain objects. However, in most research image still captured by the external camera that additional cost prohibitive. To solve this problem, in this research used Parrot AR.Drone quadcopter that has a built in camera, so not needed an extra camera. Image processing is implemented on the platform that is used to connect the ROS and quadcopter with PC using OpenCV. The method used is color filtering on the HSV color space. The results of this research in the form of a system at AR.Drone are able to detect color with accuracy of 89,6%. Tests on the system is done by testing the performance of detection distance against quadcopter with objects and color detection performance testing with a certain speed. The results is the effective range of object detection is at a distance of 1 meter and the effective speed of quadcopter done dynamically detection is with the speed of 0.6 m/s.